L1CAM expression in either metastatic brain lesion or peripheral blood is correlated with peripheral platelet count in patients with brain metastases from lung cancer - Wang, Jia-Wei; Wang, Hong-Liang; Liu, Qi; Hu, Ke; Yuan, Qing; Huang, Sheng-Kai; Wan, Jing-Hai (Frontiers in Oncology, 2022)
Background: Systemic immune-inflammation states across the heterogeneous population of brain metastases from lung cancer are very important, especially in the context of complex brain-immune bidirectional communication. Previous studies from our team and others have shown L1 cell adhesion molecule (L1CAM) is deeply involved in the aggressive phenotype, immunosuppressive tumor microenvironment(TME), and metastasis during multiple malignancies, which may lead to unfavorable outcome. However, little is known about relationship of L1CAM expression and systemic immune-inflammation macroenvironment beyond TME in brain metastases from lung cancer. Methods: Two cohorts of patients with brain metastases from lung cancer admitted to National Cancer Center, Cancer Hospital of Chinese Academy of Medical Sciences were studied in the present research. The L1CAM expression in cranial metastatic lesions by immunohistochemistry were explored in patients treated with neurosurgical resection while the L1CAM expression in peripheral blood by ELISA were tested in patients treated with non-surgical anti-tumor management. Furthermore, based on peripheral blood cell counts in CBC test, six systemic immune-inflammation biomarkers(neutrophil count, lymphocyte count, platelet count, SII, NLR, PLR) were calculated. And then the relationship between L1CAM expression and these systemic immune-inflammation biomarkers was analyzed. In addition, these systemic immune-inflammation biomarkers were also used to compare the systemic immune-inflammation states in two cohorts of patients with brain metastases from lung cancer. Results: Positive L1CAM expression in the metastatic brain lesions were accompanied with significantly increased peripheral platelet counts in patients treated with neurosurgical tumor resection(P<0.05). Similarly, in patients treated with non-surgical anti-tumor management, L1CAM expression in the peripheral blood were positively corelated with peripheral platelet counts(P<0.05). In addition, patients prepared for neurosurgical tumor resection were presented with poorer systemic immune-inflammation states in comparison with the one with non-surgical anti-tumor management, which was characterized by a significantly increase in peripheral neutrophil counts(P<0.01), SII(P<0.05) and NLR(P<0.05) levels. Conclusion: The L1CAM expression in either metastatic brain lesion or peripheral blood is positively correlated with peripheral platelet count in patients with brain metastases from lung cancer. In addition, brain metastases that are prepared for neurosurgical tumor resection show poor systemic immune-inflammation states.